2003
DOI: 10.1161/01.str.0000081982.85010.a8
|View full text |Cite
|
Sign up to set email alerts
|

Relative Value of Normalized Sonographic In Vitro Analysis of Arteriosclerotic Plaques of Internal Carotid Artery

Abstract: Background and Purpose-A close correlation between B-mode sonography and the histopathology and surface structure of plaque is rarely seen in vivo with high-grade stenoses of the extracranial carotid artery. The goal of this study was to determine whether normalized gray scale analysis and surface analysis of the plaque are capable of characterizing the attributes correctly. Methods-Optimized B-mode images of 107 carotid endarterectomy specimens were captured, and the gray scale median (GSM) was calculated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…Only 46% of the cases showed agreement between the GSM and the histopathologic findings. 30 Correlation of PDA with histology showed similar results. 25,32,33 Currently, it seems that the ability of ultrasound scan to predict signs of vulnerability in the preoperative phase is limited.…”
Section: Conventional Imaging Techniquesmentioning
confidence: 60%
See 1 more Smart Citation
“…Only 46% of the cases showed agreement between the GSM and the histopathologic findings. 30 Correlation of PDA with histology showed similar results. 25,32,33 Currently, it seems that the ability of ultrasound scan to predict signs of vulnerability in the preoperative phase is limited.…”
Section: Conventional Imaging Techniquesmentioning
confidence: 60%
“…Moreover, in up to 37% of cases, it is not possible to evaluate the plaque surface due to acoustic shadowing or a high degree of stenosis. 29,30 With the development of computer-assisted image analysis, inter-observer variability of ultrasound scan analysis has decreased. The Imaging in Carotid Angioplasty and Risk of Stroke (ICAROS) trial showed that increased echolucency of the carotid plaque, defined as a GSM of less than 25, is a risk factor for stroke during and immediately after carotid artery stenting.…”
Section: Conventional Imaging Techniquesmentioning
confidence: 99%
“…Die Übereinstimmung der Untersucher ist trotz Differenzierung sehr gut (Übersicht bei Denzel [7]). Diese Methodik setzt eine relativ aufwändige Standardisierung mit externer Bildbearbeitung (Histogrammfunktion des Adobe® Photoshop® CS) voraus (.…”
Section: Plaque-imagingunclassified
“…HITS ("high-intensity transient signals") nachweisen [11,34,35,39,46,61,75]. Auch die Angiographie und die Angioskopie spielen eine Rolle, ebenso die Doppler-Sonographie zur Aufdeckung möglicher Turbulenzphänome-ne oder die Duplexsonographie [7,10,29,30]. Die Verfechter der Operation an der Arteria carotis in Lokalanästhesie weisen darauf hin, dass in diesem Fall die neurologische Kontrolle des Patienten besonders einfach und zuverlässig durch direkte Kommunikation möglich ist [40,76].…”
Section: Treatment Of Carotid Stenosis: Carotid Surgery or Stent? In unclassified
“…The study of Alberts is not published and the inclusion criteria for the SAPPHIRE trial were restricted to the group of high-risk patients, which were not suitable for an operative treatment. [27][28][29][30].…”
Section: Argumente Für Den Karotisstentmentioning
confidence: 99%